Teixobactin kills pathogens without detectable resistance - Lewis, Kim (Henry Stewart Talks, 2015)
The high-tech & Waksman platforms, How to grow unculturable bacteria, Diffusion chamber, Petri dish and iChip comparison, The sand biofilm, Siderophores of neighbouring bacteria, Teixobactin: mechanism and efficacy
Updated at 2021/11/09